Individual, organizational and environmental factors affecting work-life balance - Kumarasamy, Mokana Muthukumar; Pangil, Faizuniah; Mohd Isa, Mohd Faizal (Canadian Center of Science and Education, 2015)
Work-life balance is very important among employee and employers in organizations.Imbalance in work-life will create a lot problem in terms of life satisfaction and workplace satisfaction.This paper is to discuss a study regarding the influence of emotional, spiritual intelligence, organizational support job engagement and technology advancement on employees work-life balance.The findings showed that emotional intelligence, job engagement and organizational support were found positively and significantly related to work-life balance. Furthermore, both technology advancement and work overload were found negatively and significantly related to work-life balance.However the findings indicated that spiritual intelligence was not significantly related to work-life balance.